2016
DOI: 10.1007/s00464-015-4568-0
|View full text |Cite
|
Sign up to set email alerts
|

Gastric bypass significantly improves quality of life in morbidly obese patients with type 2 diabetes

Abstract: Objective To evaluate the impact of Roux-en-Y gastric bypass (RYGB) on quality of life in obese diabetic patients compared to standard medical therapy for type 2 diabetes mellitus. Methods We prospectively studied two matched obese populations with type 2 diabetes. Thirty patients underwent laparoscopic RYGB and 31 received standard medical therapy combined with a diabetes support and education program (DSE), consisting of educational sessions on diet and exercise. Groups were matched by age, gender, weight,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Along with these physiological responses, improvements were observed in the quality of life of participants who performed the exercise program, especially in the physical scales of the SF36 questionnaire. Many studies have reported short-term improvements in quality of life after BS, both in the physical and mental scales 43 . However, these effects are lost in the long-term, especially in the physical domains 44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…Along with these physiological responses, improvements were observed in the quality of life of participants who performed the exercise program, especially in the physical scales of the SF36 questionnaire. Many studies have reported short-term improvements in quality of life after BS, both in the physical and mental scales 43 . However, these effects are lost in the long-term, especially in the physical domains 44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a chronic disease with a globally rising rate that reached 30.1% in 2017 [1]. Metabolic and bariatric surgery has been proved to be the most effective method not only for weight loss [2,3] but also for resolving or improving associated comorbidities [4][5][6][7] and quality of life as well as longterm mortality in obese patients [8].…”
Section: Introductionmentioning
confidence: 99%
“…It makes this study population to some extent comparable to our metabolically ill MUO subgroup, although a preexisting diabetes was not mandatory in our MUO subjects. However, data regarding the effect of an identical weight loss/weight maintenance intervention on estimates of QoL in MUO and MHO has currently not yet been available, even if QoL has developed into an important outcome measure of weight loss therapies in general [ 24 , 25 ]. It is of particular relevance for real-world settings, where changes in physical function strongly affect daily life and will therefore result in improved well-being.…”
Section: Discussionmentioning
confidence: 99%